MEDIA STEREOTYPING OF VULNERABLE GROUPS IN SERBIA - Simeunović-Patić, Biljana J (Politeia, 2021)
The paper discusses the contemporary features of stereotypes in media content, with special emphasis on practice and the consequences of stereotyping vulnerable social groups. Particular attention is paid to reviewing the prevalence and modalities of gender, racial, and ethnic stereotypes in Serbian mass media, as well as the consequences of social stereotyping affecting women, minority ethnic groups, people with mental disorders, and members of other vulnerable social groups, including their increased exposure to social marginalization, discrimination, violence, and secondary victimization. The content analysis of electronic editions of three dailies in Serbia of different newspaper format and editorial approach (Politika, Blic, and Kurir), published within the period from January 10 to February 7, 2021, was conducted to gain a closer insight into current representation, forms and other features of media stereotyping of various vulnerable social groups. The obtained findings confirm the initial assumption that stereotypes, especially gender, as well as those directed at minority ethnic groups, are expressed and routinely represented in electronic media content available to the general public, in which these groupsare continuously presented in a very narrow repertoire of social roles, primarily by tabloid dailies Additional content analysis of electronic editions of dailies in Serbia over the past five years features stereotypical portrayal of Roma, and persons with mental health disorders as categories of citizens who are predominantly represented in negative content in the media, with the absence of analytical texts and content dealing with the social background of the circumstances in which they find themselves. Furthermore, no attention is paid to their social needs, which contributes to the strengthening of stereotypes, intolerance, insensitivity, or irrational fear of members of certain vulnerable social groups. In conclusion, the importance of the role of today's mass media in maintaining, but also in deconstructing negative social stereotypes, that is, humanization of modern cultural and social space and denormalization of violence directed at vulnerable groups based on prejudice,isemphasized.
Keywords: Media; stereotypes; vulnerable social groups